Organized environmental crime: black markets in gold, wildlife, and timber - Uhm, Daan P. van (Bloomsbury Academic, 2023)
"Developing an innovative approach to understanding how organized crime groups diversify into the illegal trade in natural resources, this book looks at the convergence between environmental crime and other serious crimes"--